2018
DOI: 10.1038/s41598-018-19256-7
|View full text |Cite
|
Sign up to set email alerts
|

3D Plasmon Coupling Assisted Sers on Nanoparticle-Nanocup Array Hybrids

Abstract: Unique colorimetric optical properties of nanomaterials can effectively influence the light absorption or emission of molecules. Here, we design plasmonic substrate for surface-enhanced Raman scattering (SERS) by inducing three-dimensional (3D) hot spots on the sensing surface. The 3D hot spots are formed by the self-assembly of plasmonic nanoparticles (NPs) on a 3D plasmonic nanocup array structure. This 3D hot spot formation on the periodic nanocup arrays achieves much higher SERS enhancement factor than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…This new band is due to the dipolar plasmonic coupling between NPs. The phenomenon was well-described in the model by Kreibig and Vollmer 1 and has been corroborated with experiments and simulations in several works regarding other metals [60][61][62][63] . Thus, the spectra of Fig.…”
Section: Resultssupporting
confidence: 76%
“…This new band is due to the dipolar plasmonic coupling between NPs. The phenomenon was well-described in the model by Kreibig and Vollmer 1 and has been corroborated with experiments and simulations in several works regarding other metals [60][61][62][63] . Thus, the spectra of Fig.…”
Section: Resultssupporting
confidence: 76%
“…Many studies have reported that a significant improvement in SPR performance could be achieved by coupling GNPs to the nanoplasmonic nanocup arrays, which was attempted for the generation of denser hot spots when the plasmonic GNPs were assembled on the surface of nanocups. 27,[35][36] GNPs in the range of 20-40 nm in diameter were generally recommended for use in biological detection procedures due to their sufficient stability and immune reactivity. [37][38][39] However, only large GNPs that fit in the nanocup size can effectively help to increase the intensity of the localized electric field and improve the detection sensitivity.…”
Section: Finite-difference Time-domain (Fdtd) Simulationsmentioning
confidence: 99%
“…Plasmonic nanostructures can be implemented to generate a much enhanced evanescent field around the molecules through the excitation of so-called localized surface plasmon resonances (LSPR) on plasmonic nanostructures. The SERS EM enhancement factor can be up to 10 8 and is therefore dominant in SERS enhancement [ 5 , 6 , 7 ] In addition to the SERS EM enhancement, the CM effect that stems from the charge transfer between the molecule and the substrate can add further SERS enhancement with an enhancement factor up to 10 3 shown experimentally [ 8 , 9 , 10 ]. 2D atomic materials such as graphene and transition metal dichalcogenides (TMDs) [ 11 , 12 ] are excellent choices as SERS substrates due to their atomically flat sheet morphology that facilitates adsorption of probe molecules on the substrate surface and enables efficient charge transfer via weak interactions, such as van der Waals (vdW) or π-π interactions, between the probe molecules and substrates.…”
Section: Introductionmentioning
confidence: 99%